Floating-point–consistent cross-verification methodology for reproducible and interoperable DDA solvers with fair benchmarking - Clément Argentin; Patrick C. Chaumet; Michel Gross; Maxim A. Yurkin (Computer Physics Communications, 2026)

Temporal concentrations of Quaternary ammonium compounds in wastewater treatment effluents during the COVID-19 pandemic, 2020–2021 - Michelle L. Hladik; Michael S. Gross; Gabrielle P. Black; Dana W. Kolpin; Jason R. Masoner; Patrick J. Phillips; Paul M. Bradley; Kelly L. Smalling (Chemosphere, 2024)

Valley morphology and Quaternary seismic stratigraphy of the Manicouagan impact crater lake (Eastern Canada) - Kai‐Frederik Lenz; Andrea Catalina Gebhardt; Patrick Lajeunesse; Arne Lohrberg; Felix Gross; Sebastian Krastel (Journal of Quaternary Science, 2023)
Lakes in formerly glaciated regions can provide valuable paleoclimate archives. Lake Manicouagan (Manikuakan, according to Innu toponymy), formed in the basin of the ~214‐Ma Manicouagan impact crater of eastern Québec, is a key area for reconstructing long‐term environmental change, as it was directly affected by the Pleistocene glaciations and the waxing and waning of the Laurentide Ice Sheet. Here, we present high‐resolution seismic data revealing an overdeepened bedrock valley filled with a sedimentary sequence. We assess its potential to serve as a paleoclimate archive. The varying shape of the overdeepened valley indicates complex erosional processes. A lower narrow V‐shaped gorge is indicative of either pressurized subglacial meltwater or pre‐Quaternary fluvial erosion, or a combination of both. Three scenarios are discussed regarding deposition of the sedimentary sequence: (i) deposition only during and after retreat of the last glacial episode; (ii) deposition during multiple glacial–interglacial cycles; and (iii) deposition mainly during a subglacial lake stage. We suggest subglacial followed by proglacial sedimentation as the most probable scenario for deposition of the sedimentary succession. We recommend considering the sediments of Lake Manicouagan as a paleoclimate archive reaching back at least to 7.5 ka, but the lake also probably contains sediments deposited before the last deglacial period.

From introduction to nuisance growth: a review of traits of alien aquatic plants which contribute to their invasiveness - Andreas Hussner; Patrick Heidbüchel; Julie Coetzee; Elisabeth M. Gross (Hydrobiologia, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Genetic diversity of Aegilops L. species from Azerbaijan and Georgia using SSR markers - Mehraj Abbasov; Robert Brueggeman; John Raupp; Zeynal Akparov; Naib Aminov; David Bedoshvili; Thomas Gross; Patrick Gross; Sevda Babayeva; Vusala Izzatullayeva; Sevinj A. Mammadova; Elchin Hajiyev; et al. (Genetic Resources and Crop Evolution, 2019)

Genetic relationship of diploid wheat (Triticum spp.) species assessed by SSR markers - Mehraj Abbasov; Zeynal Akparov; Thomas Gross; Sevda Babayeva; Vusala Izzatullayeva; Elchin Hajiyev; Khanbala Rustamov; Patrick Gross; Mehmet Tekin; Taner Akar; Shiaoman Chao; Robert Brueggeman (Genetic Resources and Crop Evolution, 2018)

EUREC4A: A Field Campaign to Elucidate the Couplings Between Clouds, Convection and Circulation - Sandrine Bony; Bjorn Stevens; Felix Ament; Sebastien Bigorre; Patrick Chazette; Susanne Crewell; Julien Delanoë; Kerry Emanuel; David Farrell; Cyrille Flamant; Silke Gross; Lutz Hirsch; et al. (Surveys in Geophysics, 2017)
Trade-wind cumuli constitute the cloud type with the highest frequency of occurrence on Earth, and it has been shown that their sensitivity to changing environmental conditions will critically influence the magnitude and pace of future global warming. Research over the last decade has pointed out the importance of the interplay between clouds, convection and circulation in controling this sensitivity. Numerical models represent this interplay in diverse ways, which translates into different responses of trade-cumuli to climate perturbations. Climate models predict that the area covered by shallow cumuli at cloud base is very sensitive to changes in environmental conditions, while process models suggest the opposite. To understand and resolve this contradiction, we propose to organize a field campaign aimed at quantifying the physical properties of trade-cumuli (e.g., cloud fraction and water content) as a function of the large-scale environment. Beyond a better understanding of clouds-circulation coupling processes, the campaign will provide a reference data set that may be used as a benchmark for advancing the modelling and the satellite remote sensing of clouds and circulation. It will also be an opportunity for complementary investigations such as evaluating model convective parameterizations or studying the role of ocean mesoscale eddies in air–sea interactions and convective organization.

Impact of severe dry season on net ecosystem exchange in the Neotropical rainforest of French Guiana - DAMIEN BONAL; ALEXANDRE BOSC; STÉPHANE PONTON; JEAN‐YVES GORET; BENOÎT BURBAN; PATRICK GROSS; JEAN‐MARC BONNEFOND; JAN ELBERS; BERNARD LONGDOZ; DANIEL EPRON; JEAN‐MARC GUEHL; ANDRÉ GRANIER (Global Change Biology, 2008)
The lack of information on the ways seasonal drought modifies the CO 2 exchange between Neotropical rainforest ecosystems and the atmosphere and the resulting carbon balance hinders our ability to precisely predict how these ecosystems will respond as global environmental changes force them to face increasingly contrasting conditions in the future. To address this issue, seasonal variations in daily net ecosystem productivity (NEP d ) and two main components of this productivity, daily total ecosystem respiration ( R Ed ) and daily gross ecosystem productivity (GEP d ), were estimated over 2 years at a flux tower site in French Guiana, South America (5 °16′54″N, 52 °54′44″W). We compared seasonal variations between wet and dry periods and between dry periods of contrasting levels of intensity (i.e. mild vs. severe) during equivalent 93‐day periods. During the wet periods, the ecosystem was almost in balance with the atmosphere (storage of 9.0 g C m −2 ). Seasonal dry periods, regardless of their severity, are associated with higher incident radiation and lower R Ed combined with reduced soil respiration associated with low soil water availability. During the mild dry period, as is normally the case in this region, the amount of carbon stored in the ecosystem was 32.7 g C m −2 . Severe drought conditions resulted in even lower R Ed , whereas the photosynthetic activity was only moderately reduced and no change in canopy structure was observed. Thus, the severe dry period was characterized by greater carbon storage (64.6 g C m −2 ), emphasizing that environmental conditions, such as during a severe drought, modify the CO 2 exchange between Neotropical rainforest ecosystems and the atmosphere and potentially the resulting carbon balance.

Pan‐European δ 13 C values of air and organic matter from forest ecosystems - Deborah Hemming; Dan Yakir; Per Ambus; Mika Aurela; Cathy Besson; Kevin Black; Nina Buchmann; Regis Burlett; Alessandro Cescatti; Robert Clement; Patrick Gross; André Granier; et al. (Global Change Biology, 2005)
We present carbon stable isotope, δ 13 C, results from air and organic matter samples collected during 98 individual field campaigns across a network of Carboeuroflux forest sites in 2001 (14 sites) and 2002 (16 sites). Using these data, we tested the hypothesis that δ 13 C values derived from large‐scale atmospheric measurements and models, which are routinely used to partition carbon fluxes between land and ocean, and potentially between respiration and photosynthesis on land, are consistent with directly measured ecosystem‐scale δ 13 C values. In this framework, we also tested the potential of δ 13 C in canopy air and plant organic matter to record regional‐scale ecophysiological patterns. Our network estimates for the mean δ 13 C of ecosystem respired CO 2 and the related ‘discrimination’ of ecosystem respiration, δ er and Δ er , respectively, were −25.6±1.9‰ and 17.8 ±2.0‰ in 2001 and −26.6±1.5‰ and 19.0±1.6‰ in 2002. The results were in close agreement with δ 13 C values derived from regional‐scale atmospheric measurement programs for 2001, but less so in 2002, which had an unusual precipitation pattern. This suggests that regional‐scale atmospheric sampling programs generally capture ecosystem δ 13 C signals over Europe, but may be limited in capturing some of the interannual variations. In 2001, but less so in 2002, there were discernable longitudinal and seasonal trends in δ er . From west to east, across the network, there was a general enrichment in 13 C (∼3‰ and ∼1‰ for the 2 years, respectively) consistent with increasing Gorczynski continentality index for warmer and drier conditions. In 2001 only, seasonal 13 C enrichment between July and September, followed by depletion in November (from about −26.0‰ to −24.5‰ to −30.0‰), was also observed. In 2001, July and August δ er values across the network were significantly related to average daytime vapor pressure deficit (VPD), relative humidity (RH), and, to a lesser degree, air temperature ( T a ), but not significantly with monthly average precipitation ( P m ). In contrast, in 2002 (a much wetter peak season), δ er was significantly related with T a , but not significantly with VPD and RH. The important role of plant physiological processes on δ er in 2001 was emphasized by a relatively rapid turnover (between 1 and 6 days) of assimilated carbon inferred from time‐lag analyses of δ er vs. meteorological parameters. However, this was not evident in 2002. These analyses also noted corresponding diurnal cycles of δ er and meteorological parameters in 2001, indicating a rapid transmission of daytime meteorology, via physiological responses, to the δ er signal during this season. Organic matter δ 13 C results showed progressive 13 C enrichment from leaves, through stems and roots to soil organic matter, which may be explained by 13 C fractionation during respiration. This enrichment was species dependent and was prominent in angiosperms but not in gymnosperms. δ 13 C values of organic matter of any of the plant components did not well represent short‐term δ er values during the seasonal cycle, and could not be used to partition ecosystem respiration into autotrophic and heterotrophic components.